Building Customer Loyalty - Limakrisna, Nandan; Komar Priatna, Deden; Roswina, Winna (International Journal of Engineering and Technology, 2018)
The purpose of this research is to know marketing communications, banking in Indonesia for the debtor of credit of middle and small enterprise (MSE). Knowing credit debtor relationship of MSE woke up by banking in Indonesia. Knowing the influence of marketing communications and debtor relationship to the credit loyalty of MSE banking in Indonesia. Method of Research used are method of descriptive and explanatory survey. Unit analysis is credited debtor of MSE credit at banking in Indonesia of the size sample equal to 257 MSE. The tools of analysis in this research are structural equation model (SEM). Finding of this research is that debtor relationship and marketing communication have an effect on credit debtor loyalty of MSE, but debtor relationship of MSE has dominant effect. A novelty in this research is MSE debtor at banking in Indonesia has rarely been researched in previous studies. The contribution of this research is the debtor relationship is very important for building debtor loyalty of banking in Indonesia, especially the sustainability of the payment of installment.Â